Effect of some plant extracts in growth and development of ovary in mosquito Culex pipiens molestus Forskal - najm Gorges; amal Al Khashab (College of Education for Pure Sciences, 2010)
ABSTRACT The aim of the present study was to delect the effect of aqueous and alcoholic extracts obtioned eight spiecies of plants on the growth and development of ovaries in mosquito Culex pipiens molestus Forskal. This study included the treatment of the third larvae stage of the aforementioned with four different concentrations (160, 120, 80, 40) ppm of aqueous extracts and other four concentrations (3.0, 2.0, 1.0, 0.5) ppm of alcoholic extracts. these extracts were obtaiened from the leaves of Myrtus communis L. leaves of Ficus carica, leaves and inflourescences of Mentha piperrita and Ocimum basilicum, fruits of Rhus coriaria L., seeds of Nigella sativa, aerial parts of Hypericum crispum and leaves of Melia azedarach L., the length and width of ovarian folliecles were measured in the females obtained from the aforementioned trated larvae. The measurement were carried at adult eclosion and at12, 24, 36, 48, 72, and 96 hours after eclosion. The results of present study, in general, revealed that the best inhibition of the length of ovary took place when larvae were trated with fruits of R. coriaria extracts, where as the extracts of the N. sativa grave the best inhibition of width of ovary. this also showed that the best inhibition of the length of the follicles was when larvae were trated with the extracts of H. crispum, where as, the best inhibition of the width of ovarian follicles took place when larvae were trate with extracts of N. sativa. The result of this study also revealed that the alcololic extracts showed their superoity of inhibition, effect on that of aqueous extracts.